2016
DOI: 10.1038/srep36199
|View full text |Cite
|
Sign up to set email alerts
|

Using genome-wide CRISPR library screening with library resistant DCK to find new sources of Ara-C drug resistance in AML

Abstract: Acute myeloid leukemia (AML) can display de novo or acquired resistance to cytosine arabinoside (Ara-C), a primary component of induction chemotherapy. To identify genes capable of independently imposing Ara-C resistance, we applied a genome-wide CRISPR library to human U937 cells and exposed to them to Ara-C. Interestingly, all drug resistant clones contained guide RNAs for DCK. To avoid DCK gene modification, gRNA resistant DCK cDNA was created by the introduction of silent mutations. The CRISPR screening wa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
48
0

Year Published

2017
2017
2023
2023

Publication Types

Select...
6
2
2

Relationship

0
10

Authors

Journals

citations
Cited by 59 publications
(49 citation statements)
references
References 24 publications
1
48
0
Order By: Relevance
“…In cancer chemotherapy, dCK is an enzyme needed for phosphorylation of several deoxyribonucleosides and their nucleoside analogs such as gemcitabine and cytarabine and is known as a rate limiting enzyme in activation of these drugs. Furthermore, in addition to a report that the deficiency of dCK is involved in resistance to gemcitabine and cytarabine, it has also been reported that these drugs show very high anti-tumor efficacy in cancer cells that overexpress dCK (14)(15)(16)(17). We found for the first time that the expression levels of dCK increase with the acquisition of resistance to cetuximabin this study.…”
Section: Discussionsupporting
confidence: 70%
“…In cancer chemotherapy, dCK is an enzyme needed for phosphorylation of several deoxyribonucleosides and their nucleoside analogs such as gemcitabine and cytarabine and is known as a rate limiting enzyme in activation of these drugs. Furthermore, in addition to a report that the deficiency of dCK is involved in resistance to gemcitabine and cytarabine, it has also been reported that these drugs show very high anti-tumor efficacy in cancer cells that overexpress dCK (14)(15)(16)(17). We found for the first time that the expression levels of dCK increase with the acquisition of resistance to cetuximabin this study.…”
Section: Discussionsupporting
confidence: 70%
“…Those sgRNAs with significant changes in frequency in the pool after selection presumably target genes involved in promoting or repressing the selected phenotype. Pooled screens have been used to identify essential genes Wang et al 2014bWang et al , 2015Hart et al 2015) and genes that are involved in drug resistance (Koike-Yusa et al 2014;Shalem et al 2014;Wang et al 2014b;Hart et al 2015;Doench et al 2016;Kurata et al 2016), toxin susceptibility (Koike-Yusa et al 2014;Zhou et al 2014;Tao et al 2016), and immune response (Parnas et al 2015;Schmid-Burgk et al 2016). More recent pooled screens have used single cell sequencing to determine the impact of each sgRNA on the transcriptome rather than examining a cellular phenotype (Adamson et al 2016;Dixit et al 2016;Jaitin et al 2016;Datlinger et al 2017).…”
Section: Introductionmentioning
confidence: 99%
“…Previously, studies using CRISPR-Cas9 libraries were published. Most of these studies used the same type of genome-wide library, GeCKO CRISPR Library version 1 or 2, comprising of >120,000 sgRNAs targeting nearly the entire genome (53)(54)(55)(56). For example, Sustic et al identified the endoplasmic reticulum to nucleus signaling 1 (ERN1)-JNK-JUN pathway as a potential target for improving the anti-cancer effects of MET inhibitors in KRAS-mutated colon cancer (56).…”
Section: Dropout Viability Screening Under Drug Treatmentmentioning
confidence: 99%